2016
DOI: 10.1007/s12011-016-0649-8
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Palygorskite Inclusion on the Growth Performance, Meat Quality, Antioxidant Ability, and Mineral Element Content of Broilers

Abstract: The present study was conducted to investigate different levels of palygorskite supplementation on the growth performance, meat quality, muscular oxidative status, and mineral element accumulation of broilers. One hundred ninety-two 1-day-old Arbor Acres broiler chicks were allocated to four dietary treatments with six replicates of eight chicks per replicate. Birds in the four treatments were given a basal diet supplemented with 0, 5, 10 and 20 g/kg palygorskite for 42 days, respectively. Compared with the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 47 publications
2
12
1
Order By: Relevance
“…However, the supplementation of ZnPal in this study reduced the accumulations of Pb and Cr in the muscles, and it indicated that ZnPal supplementation could improve the safety of meat products. Similar results were also observed by Cheng et al (2016) who reported that dietary Pal inclusion, at either 10 or 20 g/kg, significantly decreased Pb accumulation in the breast or thigh muscle. Additionally, Zhang et al (2015) reported that 2% Pal supplementation reduced muscular Cd accumulation in blunt snout bream.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…However, the supplementation of ZnPal in this study reduced the accumulations of Pb and Cr in the muscles, and it indicated that ZnPal supplementation could improve the safety of meat products. Similar results were also observed by Cheng et al (2016) who reported that dietary Pal inclusion, at either 10 or 20 g/kg, significantly decreased Pb accumulation in the breast or thigh muscle. Additionally, Zhang et al (2015) reported that 2% Pal supplementation reduced muscular Cd accumulation in blunt snout bream.…”
Section: Discussionsupporting
confidence: 88%
“…In the current study, the growth performance of broilers at 42 days of age was similar among groups, and the live weight of broilers at 42 days of age in the control group and the four ZnPal groups (from 20 to 80 mg/kg Zn) was 2253, 2272, 2233, 2200, and 2309 g, respectively (Yang et al, 2016). However, dietary ZnPal supplementation increased eviscerated yield and muscle yield, indicating that the inclusion of ZnPal could improve the carcass composition of broilers.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…As showed in this study, palygorskite inclusion decreased the Pb accumulation of muscle and reduced the Cr levels in the muscle and edible viscera of Chinese mitten crabs. Similarly, Cheng et al () found that dietary addition with either 10 or 20 g/kg palygorskite reduced the Pb levels in the muscle of broilers. Studies demonstrated that Fe could compete the adsorption sites with Pb and Cr in intestine (Cerklewski, ; Hamilton, Bellamy, Valberg, & Valberg, ).…”
Section: Discussionmentioning
confidence: 86%
“…Recently, studies found that palygorskite, as a binding agent, enhanced feed pellet quality of blunt snout bream and broilers (Zhang, Yan, Zhang, Wen, & Zhou, ; Zhang et al, ). Dietary inclusion of palygorskite improved the growth performance, nutrient digestion, intestinal integrity, meat quality and mineral accumulation of blunt snout bream and broilers (Chen et al, ; Cheng et al, ; Zhang, Lv, Tang, & Wang, ; Zhang et al, ).…”
Section: Introductionmentioning
confidence: 99%